2014
DOI: 10.1371/journal.pone.0086789
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin-Based Chemotherapy Is More Beneficial in KRAS Mutant than in KRAS Wild-Type Metastatic Colorectal Cancer Patients

Abstract: To identify better regimens in currently available chemotherapy would be beneficial to KRAS mutant metastatic colorectal cancer (mCRC) patients because they have fewer treatment options than KRAS wild-type mCRC patients. Clinicopathologic features and overall survival (OS) of KRAS mutant and wild-type mCRC patients who had used oxaliplatin-based, irinotecan-based, bevacizumab-based, as well as cetuximab-based regimens were compared to those who had never-used oxaliplatin-based, irinotecan-based, bevacizumab-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
(20 reference statements)
2
8
0
Order By: Relevance
“…Lin et al suggested KRAS mutation as a predictor of oxaliplatin sensitivity in vitro by downregulation of ERCC1 [53]. Indeed, a benefit of oxaliplatin-based chemotherapy for KRAS mutated mCRC patients has been reported [41]. A recent study suggests that patients with mutations in KRAS codon 12 present a significant survival advantage compared to wild-type patients treated with irinotecan-based therapy [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al suggested KRAS mutation as a predictor of oxaliplatin sensitivity in vitro by downregulation of ERCC1 [53]. Indeed, a benefit of oxaliplatin-based chemotherapy for KRAS mutated mCRC patients has been reported [41]. A recent study suggests that patients with mutations in KRAS codon 12 present a significant survival advantage compared to wild-type patients treated with irinotecan-based therapy [54].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding standard chemotherapy response, their potential use as predictive biomarkers is not well-established. Some articles have suggested a potential role of these mutations in standard chemotherapy response [41,42], while others have refused it [17,43]. Recently, a novel role of tumor location in the outcome of patients has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of genes such as TP53, KRAS, NRAS, BRAF, and PIK3CA have implications for the outcome of targeted therapy and chemotherapy (18,(32)(33)(34)(35)(36)(37), and the analysis of KRAS, NRAS, and BRAF mutations is recommended in the NCCN guidelines to guide cetuximab treatment. In our cohort, all 21 patients with detectable ctDNA variants in pretreatment samples harbored at least one variant in the therapeutically relevant genes TP53, KRAS, BRAF, and PIK3CA.…”
Section: Discussionmentioning
confidence: 99%
“…Also they have been investigated as potential predictive markers of the response to bevacizumab or oxaliplatin, but results are controversial (8,9,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%